Faktor-Faktor yang Berhubungan (Bivariat) dengan Stigma pada Pasien TB Paru di Puskesmas Kota Gorontalo - Nur Rasdianah; Jihan AR. Gubali; Moh. Reski; Endah N. Djuwarno; Ariani H. (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Tuberculosis (TB) remains a global health problem that not only affects physical health but also has psychological and social impacts, particularly stigma experienced by patients. Stigma can lead to delayed diagnosis, poor treatment adherence, and reduced social support. However, data on the level and factors associated with stigma among pulmonary TB patients in Gorontalo City are still limited. Objective: This study aimed to determine the level of stigma and the factors associated with stigma among pulmonary TB patients at three community health centers in Gorontalo City. Methods: This study employed a quantitative descriptive design with a cross-sectional approach, conducted from January to April 2026. A total of 107 pulmonary TB patients from the North City, Dungingi, and Central City Community Health Centers were selected using purposive sampling. Data were collected using a validated Van Rie’s stigma questionnaire and analyzed using descriptive statistics and bivariate analysis (chi-square test). Results: The majority of patients (53.3%) had a moderate level of stigma. Bivariate analysis revealed that only age was significantly associated with the level of stigma (p = 0.000), while gender, education level, occupation, duration of treatment, and number of household members showed no significant relationship (p > 0.05). Based on the mean score analysis of stigma dimensions, disclosure/fear stigma was the most dominant type experienced by patients (mean = 1.77), indicating patients’ fear of disclosing their disease status due to concerns about rejection, ostracism, and social discrimination. Conclusion: Disclosure/fear stigma was identified as the most dominant type of stigma among pulmonary TB patients, and age was a significant associated factor. Stigma remains a challenge in TB management. Future research is expected to explore other factors such as knowledge about TB, family support, and community awareness, as well as local cultural contexts using qualitative approaches.